Progress in Rectal Cancer Treatment - Ceelen, Wim P. (International Scholarly Research Network, 2012)
The dramatic improvement in local control of rectal cancer observed during the last decades is to be attributed to attention to surgical technique and to the introduction of neoadjuvant therapy regimens. Nevertheless, systemic relapse remains frequent and is currently insufficiently addressed. Intensification of neoadjuvant therapy by incorporating chemotherapy with or without targeted agents before the start of (chemo)radiation or during the waiting period to surgery may present an opportunity to improve overall survival. An increasing number of patients can nowadays undergo sphincter preserving surgery. In selected patients, local excision or even a “wait and see” approach may be feasible following active neoadjuvant therapy. Molecular and genetic biomarkers as well as innovative imaging techniques may in the future allow better selection of patients for this treatment option. Controversy persists concerning the selection of patients for adjuvant chemotherapy and/or targeted therapy after neoadjuvant regimens. The currently available evidence suggests that in complete pathological responders long-term outcome is excellent and adjuvant therapy may be omitted. The results of ongoing trials will help to establish the ideal tailored approach in resectable rectal cancer.